Effect of Integrated Weed Control Options on Growth and Yield of Cassava at Kilosa District, Tanzania - Leonard, Joseph Adonia; Laswai, Emmanuel Vicent; Kudra, Abdul B.; Tryphone, George M. (Discoveries in Agriculture and Food Sciences, 2023)
Weeds are among of the major pest that hinders cassava growth and production. Also, weeds can host insect and disease pathogens, thus brings up difficulty in the growth of cassava. The effect of different weed control treatment combinations was studied at Ilonga village, Kilosa district during 2019/2020 planting season. Till only and till + Ridge, pre-emergence herbicides (Primagram Gold a.i 290 g/L S-metolachlor + 370 g/L atrazine and Oxfen a.i Oxyfluorfen 24% EC), post emergence herbicides (Force up a.i 480 g/L of Glyphosate-Isopropylamine salt and back pack weeder with modified tines were tested on Cassava variety Kiroba in a factorial experiment arranged in a randomized complete block design (RCBD) replicated three times. Combination of tillage practices and pre-emergence herbicides application increased number of days weeds took to re-emerge. The correlation analysis showed a highly significant strong positive relationship, r = 0.925, p < 0.001 and r = 0.781, p < 0.05 between cassava stem height and cassava fresh root weight, and cassava stem girth and cassava fresh root weight, respectively. Weed control combinations did not significantly affect the cassava fresh root weight, p = 0.514 and cassava biomass p = 0.732. Also weed control combinations did not significantly affect soil quality. The combination of till + ridges, application of S-metolachlor + atrazine herbicides and glyphosate provided favorable environment for cassava growth and root formation as compared to other treatment combinations. Therefore, it is recommended as a best option for controlling weeds in cassava production system.